Treatment Strategies and Outcomes of Pediatric Esthesioneuroblastoma: A Systematic Review - Safi, Chetan; Spielman, Daniel; Otten, Marc; Bruce, Jeffrey N.; Feldstein, Neil; Overdevest, Jonathan B.; Gudis, David A. (Frontiers in Oncology, 2020)
Introduction: Esthesioneuroblastoma, also known as olfactory neuroblastoma, is a small round blue cell tumor of nasal neuroepithelium first described in 1924. Though this tumor is especially rare in the pediatric population with an incidence of less than 0.1 per 100,000, it is the most common pediatric nasal cavity neoplasm. The purpose of this systematic review is to examine the treatment modalities utilized for pediatric esthesioneuroblastoma and overall survival. Methods: A systematic review was performed according to the Preferred Reporting Items for Systematic Reviews and Meta-Analysis (PRISMA) guidelines. Pubmed, EMBASE, and Ovid MEDLINE databases were queried for studies pertinent to treatment modalities for pediatric esthesioneuroblatoma and survival outcomes. Results: 276 articles were identified, with seven meeting inclusion criteria. Ninety-four patients with an age range of 0.9 to twenty-one years old with esthesioneuroblastoma were included. Nearly 90% of patients were of stage Kadish B or C at time of presentation, while 20% presented with cervical lymphadenopathy. Only about 10% of patients underwent single modality therapy. Overall, five-year survival ranged from 44% to 91% with a median follow-up of 3 to 13 years. Conclusion: Children with esthesioneuroblastoma usually present at an advanced stage and undergo multi-modality therapy at a higher rate than adult patients. There is a wide range of documented overall survival though this lack of precision could be due to a paucity of patients.